Bioenergy from Biofuel Residues and Wastes. (1st October 2017) - Choudri, B.S.; Charabi, Yassine; Baawain, Mahad; Ahmed, Mushtaque
Abstract : This review includes works published in the general scientific literature during 2016 on the production of bioenergy and biofuel from waste residues generated during bioethanol and biodiesel production with a brief overview of current and emerging feedstocks. A section of this review summarizes literature on culturing algae for biofuels including bioreactors and open pond cultivation systems with the utilization of inorganic and organic sources of nutrients. New methods applicable to the mass culture of algae are highlighted. Algal cell harvesting and oil extraction techniques are discussed along with policies and economics.